2021
DOI: 10.4102/sajpsychiatry.27i0.1580
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, risk and understandings of the COVID-19 pandemic in urban South Africa

Abstract: Background: How people perceive the coronavirus disease 2019 (COVID-19) pandemic and understand their risk can influence their health, behaviours and overall livelihood. The disease's novelty and severity have elicited a range of attitudes and perspectives countrywide, which consequently influence the public's adherence to public health prevention and treatment guidelines.Aim: To investigate perceptions, experiences and knowledge on COVID-19 in a communitybased cohort study.Setting: Adults living in Soweto in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In addition to this socio-economic disparity, the effects of the pandemic have been perceived differently by the various socio-economic groups across South Africa. This is also confirmed by studies such as those by Kim et al (2021) [11] who found in a study of 391 individuals in a part of Gauteng that socio-economic variables such as age, gender, level of education and household density played a significant role in shaping people's perceptions about the pandemic. Also, a Human Sciences Research Council (HSRC) study by Reddy et al (2020) [12] found differences in perceptions of COVID-19 amongst the urban population, particularly with those living in informal settlements perceiving COVID-19 to be a major cause of their deteriorating living conditions as it resulted in their limited access to food and exacerbated their financial conditions [12] Spatial variations associated with socio-economic risk in COVID-19 studies have been conducted to identify areas with greater likelihood to be affected by the pandemic in order to optimise control programmes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…In addition to this socio-economic disparity, the effects of the pandemic have been perceived differently by the various socio-economic groups across South Africa. This is also confirmed by studies such as those by Kim et al (2021) [11] who found in a study of 391 individuals in a part of Gauteng that socio-economic variables such as age, gender, level of education and household density played a significant role in shaping people's perceptions about the pandemic. Also, a Human Sciences Research Council (HSRC) study by Reddy et al (2020) [12] found differences in perceptions of COVID-19 amongst the urban population, particularly with those living in informal settlements perceiving COVID-19 to be a major cause of their deteriorating living conditions as it resulted in their limited access to food and exacerbated their financial conditions [12] Spatial variations associated with socio-economic risk in COVID-19 studies have been conducted to identify areas with greater likelihood to be affected by the pandemic in order to optimise control programmes.…”
Section: Introductionsupporting
confidence: 68%
“…For Indians/Asians, living standards were a significant predictor of life satisfaction [30] These findings point to the importance of socio-demographic variables in predicting satisfaction with life. Socio-demographic variables have been shown in various studies to have a spatial bearing in South Africa, and to be important predictors of vulnerability [11,12]. The choropleth map depicted in Figure 3 shows the aggregated modelled results for life satisfaction during COVID-19.…”
Section: Covid-19 and Overall Satisfaction With Life In Gautengmentioning
confidence: 99%
“…Additionally, comradery fostered between co-workers provided both emotional support and functional adaptations such as sharing or swapping shifts, which are associated with improved wellbeing through decreased burnout [ 49 ] and mental health issues [ 50 , 51 ], and increased job retention [ 19 , 52 ]. Communication between colleagues provided interpersonal connection and knowledge, which is associated with increased confidence [ 7 , 13 15 , 19 , 28 , 30 , 31 ]. Good communication and collaboration with management, described as being transparent, clear, and informative were also a source of support, possibly providing a buffer between traumatic stress at work and burnout or intent to resign [ 13 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial stress from the COVID‐19 pandemic was assessed using a locally‐developed, 20‐item Likert‐based scale that queried the severity of stress brought on by 20 separate experiences and conditions over the course of the pandemic since March 2020 to the time of data collection (Kim, n.d.). These included experiences such as financial strain, food insecurity, inability to socialize, and concerns about one's future, among others.…”
Section: Methodsmentioning
confidence: 99%